Effects of Material and Doping Profile Engineering of Source Junction on Line Tunneling FET Operations - Ko, Min Ki; Kim, Jang Hyun; Kim, Garam (Journal of Semiconductor Technology and Science, 2023)
—The electrical characteristics of line tunneling field-effect transistor (LTFET) is analyzed by technology computer-aided design (TCAD) simulation when the material and doping concentration at the end of the source junction are changed. Partial use of SiGe at the end of Ge source can reduce power consumption by reducing off-state current (IOFF) while maintaining on-state current (ION). In addition, if the doping concentration at the end of the source is lowered, ION is improved and electrical characteristics suitable for high performance applications can be obtained. But these two methods also have disadvantages. In the case of lowering doping concentration at the end of the source, IOFF is higher than conventional LTFET. In the case of Partial use of SiGe at the end of Ge source, ION is lower than conventional LTFET. However, combining these two methods can overcome each other’s disadvantages with the advantages of the other method.
Keywords: Line tunneling FET; On-off current ratio (ION/IOFF); ON/OFF current ratio; On/off-current ratios; Partial light doping source; Partial sige source; Sub-threshold swing(ss); Subthreshold swing; Tunneling field-effect transistor; Tunneling field-effect transistors; line tunneling FET (LTFET); on-off current ratio (ION/IOFF); partial light doping source; partial SiGe source; subthreshold swing (SS); Tunneling field-effect transistor (TFET)